Metformin promotes autophagy and apoptosis in esophageal squamous cell carcinoma by downregulating Stat3 signaling - Feng, Y (Nature Publishing Group, 2014)
The antidiabetic drug metformin exerts chemopreventive and antineoplastic effects in many types of malignancies. However, the mechanisms responsible for metformin actions appear diverse and may differ in different types of cancer. Understanding the molecular and cellular mechanisms specific for different cancers is important to optimize strategy for metformin treatment in different cancer types. Here, we investigate the in vitro and in vivo effects of metformin on esophageal squamous cell carcinoma (ESCC) cells. Metformin selectively inhibited cell growth in ESCC tumor cells but not immortalized noncancerous esophageal epithelial cells. In addition to apoptosis, metformin triggered autophagy. Pharmacological or genetic inhibition of autophagy sensitized ESCC cells to metformin-induced apoptotic cell death. Mechanistically, signal transducer and activator of transcription 3 (Stat3) and its downstream target Bcl-2 was inactivated by metformin treatment. Accordingly, small interfering RNA (siRNA)-mediated Stat3 knockdown enhanced metformin-induced autophagy and apoptosis, and concomitantly enhanced the inhibitory effect of metformin on cell viability. Similarly, the Bcl-2 proto-oncogene, an inhibitor of both apoptosis and autophagy, was repressed by metformin. Ectopic expression of Bcl-2 protected cells from metformin-mediated autophagy and apoptosis. In vivo, metformin downregulated Stat3 activity and Bcl-2 expression, induced apoptosis and autophagy, and inhibited tumor growth. Together, inactivation of Stat3-Bcl-2 pathway contributes to metformin-induced growth inhibition of ESCC by facilitating crosstalk between apoptosis and autophagy.